Intensifying service delivery: are procurement framework agreements relevant? - Tinotenda Fredrick Munyimi; Lovemore Chikazhe (Cogent Business & Management, 2024)
Around the globe, public management research covers little enquiry on advancing service delivery in service delivery organisations like local authorities. Yet, the call for timely service delivery within local authorities is on the increase, there is need for flexible procurement methods which facilitate quick deliveries to advance expected service delivery by residents. Against this backdrop, this research undertook a survey to answer if procurement framework agreements advance service delivery moving forward. Drawing on a unique sample of 55 local authorities' procurement practitioners in Zimbabwe, the research findings point to the likely hood of advancing service delivery greater through use of procurement framework agreements. Since lack of practical know-how is the main reason for slow use of this method, public procurement authorities should focus on procurement cadre development, capacity building and engaging market suppliers. Thus, this research uncovers fresh insights on how procurement practitioners can leverage on procurement framework agreements to enhance expected service delivery in local authorities and put forward the call for the urgent integration of the procurement method going forward.
Keywords: 650; procurement framework agreements; service delivery; local government; local authority; public sector